2008
DOI: 10.1007/s11295-008-0156-y
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis for aphid resistance and growth traits in apple

Abstract: The rosy apple aphid (Dysaphis plantaginea), the leaf-curling aphid (Dysaphis cf. devecta) and the green apple aphid (Aphis pomi) are widespread pest insects that reduce growth of leaves, fruits and shoots in apple (Malus × domestica). Aphid control in apple orchards is generally achieved by insecticides, but alternative management options like growing resistant cultivars are needed for a more sustainable integrated pest management (IPM). A linkage map available for a segregating F 1 -cross of the apple cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…QTLs whose expression differs across environments seem to be the rule rather than the exception in tree species (Asíns et al, 1994;Emebiri et al, 1998;García et al, 2000). Concerning the influence of growth characteristics of the host plant on resistance to aphid infestation, the effects of neighbouring tree infestation levels and/or different climatic conditions at the experimental site may impede the identification of genetically based resistance (Stoeckli et al, 2008). In this study, significant QTLs common to both trials were detected, although the test conditions varied (greenhouse versus shelter, saplings versus 2-year-old trees, monoclonal aphid colony versus a mixture of genotypes for infestation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QTLs whose expression differs across environments seem to be the rule rather than the exception in tree species (Asíns et al, 1994;Emebiri et al, 1998;García et al, 2000). Concerning the influence of growth characteristics of the host plant on resistance to aphid infestation, the effects of neighbouring tree infestation levels and/or different climatic conditions at the experimental site may impede the identification of genetically based resistance (Stoeckli et al, 2008). In this study, significant QTLs common to both trials were detected, although the test conditions varied (greenhouse versus shelter, saplings versus 2-year-old trees, monoclonal aphid colony versus a mixture of genotypes for infestation).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on trees have been far less abundant. In apple, Stoeckli et al (2008) studied the relationship between aphid resistance and plant growth traits because, in addition to variations in plant chemistry, shoot growth characteristics may also influence plant susceptibility to pests. The authors identified significant QTLs for resistance to three aphid species and QTLs for plant shoot length and stem diameter.…”
Section: Introductionmentioning
confidence: 99%
“…devecta Wlk. ), and the Russian wheat aphid (Diuraphis noxia Mordvilko) [26]- [31] as well as diseases such as apple scab (Venturia inaequalis Cooke), powdery mildew (Podosphaera leucotricha Ellis and Everh. ), and fire blight (Erwinia amylovora Burrill) [29] [32] [33] [34].…”
Section: Introductionmentioning
confidence: 99%
“…Some quantitative trait loci (QTLs) were identified associated with aphid resistance in apple. Molecular markers were discovered linked to QTLs for resistance to the rosy apple aphid, the leaf-curling aphid and the green apple aphid (Stoeckli et al, 2008). Recently, progresses have been achieved regarding the development of molecular markers associated with WAA resistance genes (i.e.…”
Section: Introductionmentioning
confidence: 99%